Methods for the examination of organismal diversity in soils and sediments (CAB International in association with United Nations Educational, Scientific, and Cultural Organization and the International Union of Biological Sciences, 1996)
This book provides an authoritative manual of the techniques for ascertaining what organisms are present in soil samples. It has been developed as part of a project initiated by the International Union of Biological Sciences (IUBS), supported by UNESCO. It covers both soil organisms and those inhabiting freshwater and marine sediments, from microbes (bacteria, algae, fungi, etc.) to macrofauna (earthworms, nematodes, molluscs, etc.). The book makes a major contribution to the literature and is indispensable for soil and aquatic biologists and ecologists, as well as those with a broader interest in biodiversity and environmental sciences.